Governing the heart and soul : human governance vs corporate governance - New Straits Times, (2011)
WHEN she was dean of the Graduate School of Management (GSM) at Universiti Putra Malaysia (UPM), previously, Associate Professor Dr Arfah Salleh had the opportunity to dialogue on her worldview of science with a professor of risk management who, though a trained nuclear physicist, had successfully established a name in the corporate world at board membership level and as an entrepreneur.